The Influence of Counseling Toward The Level of Knowledge About Contraception Tool in Family Planning Acceptor in Public Health Centre of Kassi-Kassi Makassar - Nurul Fitri Sugiarti Syam; Rahmawati Rahmawati; Abdul Malik Iskandar (The International Science of Health Journal, 2023)
The less knowledge of mother about the celection of contraception type that they are going to consume is caused by the less counseling from paramedic particularly midwives. Childbearing age couple a who visit the health service centre commonly choose general contraception tool such as pill and injection, it is caused by uneffective counseling about contraception tool. This study aims at knowing the factors of infection in postpartum period. Type of research in analytical survey research with cross sectional study research. Total sample is 55 people who were choosen by using purposive sampling technique. Data collection did by delivering questionnaire as primary data and the data analysis did by using SPSS program and were analyzed with chi square test with level of significance ?=0,05. Based on the continuity correction, it showed the result of cross test where there I relationship between counseling and the level of knowledge where the value of p ? value or =0,002 <?=0,05. It is suggested to mother to use contraception which met to their urge and not to focus with one certain contraception tool and use it in long period.